2017
DOI: 10.1002/2017jb014474
|View full text |Cite
|
Sign up to set email alerts
|

Magnetotelluric Imaging of Lower Crustal Melt and Lithospheric Hydration in the Rocky Mountain Front Transition Zone, Colorado, USA

Abstract: We present an electrical resistivity model of the crust and upper mantle from two‐dimensional (2‐D) anisotropic inversion of magnetotelluric data collected along a 450 km transect of the Rio Grande rift, southern Rocky Mountains, and High Plains in Colorado, USA. Our model provides a window into the modern‐day lithosphere beneath the Rocky Mountain Front to depths in excess of 150 km. Two key features of the 2‐D resistivity model are (1) a broad zone (~200 km wide) of enhanced electrical conductivity (<20 Ωm) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
33
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(40 citation statements)
references
References 93 publications
6
33
1
Order By: Relevance
“…As argued by Chatterjee et al (), Ferri et al (), and others (e.g., Christensen, ; Dawson et al, ; Hacker et al, ; Lin et al, ; Mueller & Massonne, ; Nakajima et al, ; Owens & Zandt, ; Xu et al, ), when melting commences both V p and V s are decreased, but V s is decreased more rapidly than V p , thus increasing the total V p / V s ratio. These observations and interpretation are consistent with the recent MT results by Feucht et al (), who imaged an anisotropic high conductivity region in the middle and lower crust of the SRM, which they interpreted as strike‐parallel fractures/dikes along a north‐south direction containing melts and/or aqueous fluids. Although the resolution of our parameterization does not allow us to capture such small‐scale fracture zones, we note that the regions of significantly high V p / V s values beneath the SRM and the RGR system (latitude ∼39N and longitude ∼106W; e.g., profiles B, C, D, E, F, G, and H in Figure ) coincide well with the regions of high conductivity reported by Feucht et al ().…”
Section: Main Results and Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…As argued by Chatterjee et al (), Ferri et al (), and others (e.g., Christensen, ; Dawson et al, ; Hacker et al, ; Lin et al, ; Mueller & Massonne, ; Nakajima et al, ; Owens & Zandt, ; Xu et al, ), when melting commences both V p and V s are decreased, but V s is decreased more rapidly than V p , thus increasing the total V p / V s ratio. These observations and interpretation are consistent with the recent MT results by Feucht et al (), who imaged an anisotropic high conductivity region in the middle and lower crust of the SRM, which they interpreted as strike‐parallel fractures/dikes along a north‐south direction containing melts and/or aqueous fluids. Although the resolution of our parameterization does not allow us to capture such small‐scale fracture zones, we note that the regions of significantly high V p / V s values beneath the SRM and the RGR system (latitude ∼39N and longitude ∼106W; e.g., profiles B, C, D, E, F, G, and H in Figure ) coincide well with the regions of high conductivity reported by Feucht et al ().…”
Section: Main Results and Discussionsupporting
confidence: 91%
“…These observations and interpretation are consistent with the recent MT results by Feucht et al (), who imaged an anisotropic high conductivity region in the middle and lower crust of the SRM, which they interpreted as strike‐parallel fractures/dikes along a north‐south direction containing melts and/or aqueous fluids. Although the resolution of our parameterization does not allow us to capture such small‐scale fracture zones, we note that the regions of significantly high V p / V s values beneath the SRM and the RGR system (latitude ∼39N and longitude ∼106W; e.g., profiles B, C, D, E, F, G, and H in Figure ) coincide well with the regions of high conductivity reported by Feucht et al (). The spatial correlation between low wavespeeds, high V p / V s , elevated temperatures (see Figure ) and the locations of Cenozoic volcanism in the SRM and margins of the CP, offers compelling support for the occurrence of partial melting within the middle to lower crustal depths in these regions (e.g., beneath the Jemez zone and the SRM).…”
Section: Main Results and Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Another key feature of our interpretation is that, despite significant variability in inherited lithospheric structure, crustal thickness, width of extension, and surface geology along the axis of the Rio Grande rift, the resistivity structure of the lower crust in this tectonic regime appears to be remarkably uniform (Figure ). The low resistivity zone that we image in this study has been observed previously in regional (Feucht et al, ) and local (Hermance & Pedersen, ; Nettleton, ) studies of the Rio Grande rift conductivity structure. The addition of the two wide‐aperture, deep sensing MT profiles presented here allows us to put these previous observations into a larger tectonic context.…”
Section: Discussionsupporting
confidence: 85%
“…In summary, it is difficult to differentiate between partial melt and free saline fluids in a tectonic environment in which both are reasonable (e.g., Feucht et al, ; Li et al, ). That the electrical conductivity of the lower crustal anomaly appears to be enhanced in the direction parallel to the rift axis in the anisotropic model (e.g., Figure b) suggests the presence of partial melt within a network of vertical, rift‐parallel lenses.…”
Section: Discussionmentioning
confidence: 99%